A moisture and heat aging resistant ABS material and a preparation method thereof
Patent Information
- Application Number
- CN202611285502.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-24
- Publication Date
- 2026-10-30
AI Technical Summary
其次,简单的抗氧剂复配或纳米填料添加缺乏对相界面这一薄弱环节的针对性设计,无法有效阻断水汽沿界面的定向渗透
(1)在相界层级,本发明通过γ-缩水甘油醚氧丙基三甲氧基硅烷对疏水气相二氧化硅进行环氧改性,利用引入的环氧基团与本体法ABS树脂中SAN树脂的强极性腈基孤对电子之间的强偶极-偶极相互作用,克服了常规纳米填料在聚合物基体中易团聚、易迁移的缺陷,使纳米二氧化硅牢固钉扎在相界微缺陷处。这不仅实现物理上阻碍水汽渗透,更显著增强了相间粘合力,有效抑制了冷热交变应力下的微裂纹扩展。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of ABS material technology, and more particularly to an ABS material resistant to damp heat aging and its preparation method. Background Technology
[0002] ABS (acrylonitrile-butadiene-styrene copolymer) is a widely used thermoplastic engineering plastic, consisting of a styrene-acrylonitrile copolymer (SAN resin) as the continuous phase and polybutadiene rubber as the dispersed phase, forming a typical "island structure". Thanks to the rigidity, chemical resistance, and surface gloss provided by SAN resin, and the excellent impact toughness imparted by the polybutadiene rubber phase, ABS plays an important role in electronics, home appliances, and automotive parts. In particular, ABS is commonly used for non-electrical structural parts such as hair dryer housings, nozzles, handles, and decorative rings because of its good molding processability, dimensional stability, and ease of surface coloring and painting, meeting the aesthetic design and large-scale production requirements of home appliances. However, the polybutadiene rubber phase of ordinary ABS contains a large number of unsaturated double bonds, making it prone to oxidative degradation under the influence of heat, oxygen, and light. The aging process is significantly accelerated, especially when moisture and heat-oxygen conditions are coupled, limiting its long-term use in high-temperature and high-humidity environments such as bathrooms.
[0003] To address the issue of damp heat aging in ABS materials, existing technologies primarily modify them in two ways. The first is to optimize the antioxidant system by adding a compound of hindered phenolic primary antioxidants and phosphite auxiliary antioxidants to improve the stability of the matrix under thermo-oxidative conditions. Some solutions also introduce ultraviolet absorbers to combat photo-aging or add lubricants to improve processing performance. The second approach draws on the experience of damp heat resistance modification of polycarbonate / ABS alloys (PC / ABS) by adding carbodiimide anti-hydrolysis agents. These anti-hydrolysis agents have proven effective in PC / ABS systems containing ester bonds, delaying damp heat aging by capturing carboxyl groups and inhibiting ester bond hydrolysis. Some patent documents, such as Chinese patent CN111004489A, have disclosed technical solutions for using carbodiimide in ABS-related systems, attempting to solve the damp heat resistance problem of ABS.
[0004] However, the aforementioned existing technologies all have significant shortcomings. First, ABS and PC / ABS differ fundamentally in molecular structure and degradation mechanism—ABS molecular chains do not contain easily hydrolyzed ester bonds, and its hygrothermal aging stems from the thermo-oxidative degradation of unsaturated double bonds in polybutadiene and the capillary penetration of water vapor along the SAN / rubber interface. The target of carbodiimide-based anti-hydrolysis agents does not match the actual degradation pathway of ABS, making it difficult to provide effective protection; their alkalinity may even catalyze the degradation of the ABS matrix, causing the material's performance to decline rather than improve. Second, simple antioxidant compounding or nanofiller addition lacks targeted design for the weak link of the phase interface, failing to effectively block the directional penetration of water vapor along the interface. Furthermore, hair dryers in bathrooms face multiple synergistic effects of alternating hygrothermal heat (55℃ / 95%RH), intermittent thermal shock, and alcohol media in hairspray. Existing technologies generally do not systematically optimize formulations and processes for this complex and demanding application scenario, making it difficult to simultaneously meet the comprehensive performance requirements of high impact strength retention, low color difference, and stable insulation resistance after long-term hygrothermal aging. Summary of the Invention
[0005] To solve the above-mentioned technical problems, the present invention provides an ABS material resistant to damp heat aging, which is prepared from raw materials comprising the following components in parts by weight: 65-78 parts of bulk ABS resin (rubber content 15-18%, acrylonitrile content 28-32%). 8-18 parts of high-rubber ABS powder (polybutadiene content 55-65%); by increasing the rubber content of the system, the toughness loss caused by wet heat aging is compensated, and the dense rubber structure of the high-rubber powder helps to delay the diffusion of water and oxygen into the particle interior. 0.15-0.4 parts of fluorocarbon surfactant; during melt processing and use, it migrates to the surface along with the lubricant system and forms a hydrophobic film; 0.8-2.0 parts of epoxy-based silane-modified hydrophobic fumed silica; 0.8-1.5 parts of calcium stearate; 0.5-1.0 parts of compound antioxidant; 0.3-0.6 parts of lubricant.
[0006] The epoxy-modified hydrophobic fumed silica is prepared by grafting fumed silica that has been surface-treated with dimethyl dichlorosilane with γ-glycidoxypropyltrimethoxysilane, and has an epoxy value of 0.15-0.25 mmol / g.
[0007] This invention also provides a method for preparing the material, which involves melt blending and extrusion using a twin-screw extruder, comprising the following steps: (1) Add bulk ABS resin, ABS high-rubber powder, calcium stearate, composite antioxidant and lubricant to the twin-screw extruder through the main feed port; (2) Fluorocarbon surfactant and epoxy silane modified hydrophobic fumed silica are added at the end of the plasticizing section through the side feed port. The temperature of this section is 180-200℃. (3) During the melt blending extrusion process, the barrel vacuum degree is ≥0.085MPa and the die head temperature is 200-215℃; (4) The extrudate is granulated underwater and dried to obtain the ABS material that is resistant to damp heat aging.
[0008] Preferably, the fluorocarbon surfactant is perfluorohexyl ethyl sulfonamide propyl betaine (FTAB), which is a C6 short-chain perfluoroalkyl betaine surfactant that meets environmental regulations.
[0009] Preferably, the composite antioxidant is composed of hindered phenolic antioxidant 1076, phosphite antioxidant 168 and ultraviolet absorber UV-234 in a mass ratio of (0.2-0.4):(0.2-0.4):(0.1-0.2).
[0010] Preferably, the lubricant is ethylene bis-stearamide (EBS).
[0011] Preferably, the preparation method of the epoxy silane modified hydrophobic fumed silica is as follows: 100 parts of fumed silica raw powder surface-treated with dimethyl dichlorosilane and 1.5-3 parts of γ-glycidyl etheroxypropyltrimethoxysilane are refluxed in toluene for 3-5 hours, filtered, and dried at 60-100℃ to obtain the product.
[0012] Furthermore, this invention also seeks protection for the application of the aforementioned moisture- and heat-resistant ABS material in non-electrified structural components of a hair dryer that operates intermittently in a bathroom environment, wherein the non-electrified structural components are nozzles, handle housings, or decorative rings.
[0013] The beneficial effects of this invention are as follows: (1) At the phase boundary level, this invention uses γ-glycidoxypropyltrimethoxysilane to epoxy modify hydrophobic fumed silica. The strong dipole-dipole interaction between the introduced epoxy groups and the lone pair electrons of the strongly polar nitrile groups in the bulk ABS resin overcomes the defects of conventional nanofillers that are prone to aggregation and migration in the polymer matrix, thus firmly anchoring the nano-silica at the micro-defects at the phase boundary. This not only physically hinders water vapor penetration but also significantly enhances interphase adhesion, effectively suppressing the propagation of microcracks under alternating thermal stress.
[0014] (2) At the surface level, the perfluorohexyl ethyl sulfonamide propyl betaine introduced in this invention has extremely low surface free energy and excellent chemical stability under humid and hot conditions. Unlike static hydrophobic coatings, this fluorocarbon surfactant continuously migrates and accumulates at the material-air interface during processing and subsequent use due to thermodynamic incompatibility, forming a self-replenishing nano-hydrophobic film. This film keeps the water contact angle on the material surface stably above 105°, preventing bathroom condensate from spreading and adsorbing, greatly shortening the residence time of liquid water on the shell surface, and blocking the initial path of water vapor penetration into the substrate from the thermodynamic source.
[0015] (3) At the matrix level, this invention breaks through the functional scope of calcium stearate merely as a lubricant, exploring its core function of chemical blocking. The trace amounts of carboxylic acid produced by the oxidation of polybutadiene can autocatalyze and accelerate the degradation chain reaction, posing a hidden danger. The calcium stearate of this invention, through Ca... 2+ It reacts with these carboxylic acids to form stable and harmless calcium carboxylate salts. This not only interrupts the acidic autocatalytic cycle but also avoids the degradation of insulation performance caused by the precipitation of ionic impurities. Detailed Implementation
[0016] To further illustrate the technical means and effects of the present invention in achieving the intended purpose, the following detailed description of the specific implementation methods, structures, features and effects of the present invention, in conjunction with preferred embodiments, is provided below.
[0017] The raw material sources for the following examples and comparative examples are: Bulk-processed ABS resin: Formosa Plastics (Taiwan), grade AG15A1, rubber content 16%, acrylonitrile content 30%; ABS high-polymer powder, Kumho Chemical Co., Ltd., South Korea, grade HR-181, polybutadiene content 60%; Perfluorohexylethylsulfonamide propyl betaine, 3M Company, USA, brand name FC-4430; Fumed silica surface-treated with dimethyldichlorosilane (AEROSIL R972): Evonik Industries, brand name AEROSIL R972; Calcium stearate: Sinopharm Chemical Reagent Co., Ltd., analytical grade; Dicarbodiimide anti-hydrolysis agent, Rhein Chemicals, brand name Stabaxol P.
[0018] Preparation Example 1: Preparation of epoxy-based silane-modified hydrophobic fumed silica 100 parts of dimethyldichlorosilane-treated fumed silica (AEROSIL R972) powder and 2.0 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added to 500 parts of toluene, stirred and dispersed evenly, and refluxed at 110℃ for 4 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was washed twice with a small amount of anhydrous ethanol and dried in a forced-air drying oven at 80℃ to constant weight to obtain epoxy-silane-modified hydrophobic fumed silica. The epoxy value was determined to be 0.20 mmol / g by hydrochloric acid-acetone titration.
[0019] Preparation Example 2: 100 parts of dimethyldichlorosilane-treated fumed silica (AEROSIL R972) powder and 1.5 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added to 500 parts of toluene, stirred and dispersed evenly, and then refluxed at 110℃ for 3 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was washed twice with a small amount of anhydrous ethanol. It was then dried in a forced-air drying oven at 60℃ to constant weight to obtain epoxy-silane-modified hydrophobic fumed silica. The epoxy value was determined to be 0.15 mmol / g by hydrochloric acid-acetone titration.
[0020] Preparation Example 3 100 parts of dimethyldichlorosilane-treated fumed silica (AEROSIL R972) powder and 3.0 parts of γ-glycidyl etheroxypropyltrimethoxysilane were added to 500 parts of toluene, stirred and dispersed evenly, and then refluxed at 110℃ for 5 hours. After the reaction was completed, the mixture was cooled to room temperature, filtered, and the filter cake was washed twice with a small amount of anhydrous ethanol and dried in a forced-air drying oven at 100℃ to constant weight to obtain epoxy-silane-modified hydrophobic fumed silica. The epoxy value was determined to be 0.25 mmol / g by hydrochloric acid-acetone titration.
[0021] Example 1 The formulation consists of the following parts by weight: 72 parts bulk ABS resin, 12 parts high-resin ABS powder, 0.25 parts perfluorohexyl ethyl sulfonamide propyl betaine, 1.2 parts epoxy silane-modified hydrophobic fumed silica obtained in Preparation Example 1 above, 1.0 part calcium stearate, 0.7 parts composite antioxidant (composed of 0.3 parts hindered phenolic antioxidant 1076, 0.3 parts phosphite antioxidant 168, and 0.1 parts ultraviolet absorber UV-234), and 0.4 parts ethylene bis-stearamide.
[0022] Preparation method: Melt blending extrusion was performed using a co-rotating twin-screw extruder. Bulk-processed ABS resin, high-resin ABS powder, calcium stearate, composite antioxidant, and ethylene bis-stearamide were added to a high-speed mixer and mixed at room temperature for 5 minutes. The mixture was then fed into the twin-screw extruder through the main feed port. Perfluorohexyl ethyl sulfonamide propyl betaine was premixed with epoxy-modified hydrophobic fumed silica and added through a side feed port at the end of the plasticizing section (zone 6), where the temperature was 195°C. The barrel temperature zones were set as follows: Zone 1 165°C, Zone 2 180°C, Zone 3 195°C, Zone 4 205°C, Zone 5 205°C, Zone 6 195°C, and the die head temperature was 205°C. The screw speed was 400 rpm. During melt extrusion, a two-stage vacuum devolatilization process was initiated, with a vacuum degree of 0.088 MPa. The extrudate was then underwater pelletized and dried at 80°C for 4 hours to obtain the moisture-resistant aging-resistant ABS material. Before injection molding, the granules are dried again at 80℃ for 2 hours, and the injection temperature is 230-245℃.
[0023] The material obtained in Example 1 was prepared into a sample with dimensions of 80 mm × 10 mm × 4 mm, and analyzed using an XPS energy dispersive spectroscopy system with Ar... + Ion beam etching was performed layer by layer on the sample surface, and the F 1s peak and F / C atomic ratio were collected at different depths. In the original sample, the F 1s characteristic peak (binding energy 688 eV) belonging to the CF bond was detected in the near-surface region (etching depth 0-5 nm), with an F / C atomic ratio as high as 0.12-0.15. At an etching depth of 50 nm, the F signal intensity decreased sharply, and the F / C atomic ratio decreased by 60-70% near the surface. After 500 hours of humid heat aging at 85℃ / 85%RH, the near-surface F / C atomic ratio of the original sample decreased by only 9%, still maintaining significant hydrophobic characteristics.
[0024] Example 2 The formula composition by weight is as follows: 78 parts bulk ABS resin, 8 parts high-resin ABS powder, 0.15 parts perfluorohexyl ethyl sulfonamide propyl betaine, 0.8 parts epoxy silane modified hydrophobic fumed silica, 0.8 parts calcium stearate, 0.5 parts composite antioxidant (composed of 0.2 parts hindered phenolic antioxidant 1076, 0.2 parts phosphite antioxidant 168, and 0.1 parts ultraviolet absorber UV-234), and 0.3 parts ethylene bis-stearamide.
[0025] The preparation method is the same as in Example 1.
[0026] Example 3 The formula composition by weight is as follows: 65 parts bulk ABS resin, 18 parts high-resin ABS powder, 0.4 parts perfluorohexyl ethyl sulfonamide propyl betaine, 2.0 parts epoxy silane modified hydrophobic fumed silica, 1.5 parts calcium stearate, 1.0 part composite antioxidant (composed of 0.4 parts hindered phenolic antioxidant 1076, 0.4 parts phosphite antioxidant 168, and 0.2 parts ultraviolet absorber UV-234), and 0.6 parts ethylene bis-stearamide.
[0027] The preparation method is the same as in Example 1.
[0028] Example 4 The formulation is the same as in Example 1.
[0029] Preparation Method: The process involves melt blending and extrusion using a co-rotating twin-screw extruder. Bulk-processed ABS resin, high-resin ABS powder, calcium stearate, composite antioxidant, and ethylene bis-stearamide are added to a high-speed mixer and mixed at room temperature for 5 minutes. The mixture is then fed into the twin-screw extruder through the main feed port. Perfluorohexyl ethyl sulfonamide propyl betaine is premixed with epoxy-modified hydrophobic fumed silica and added through a side feed port at the end of the plasticizing section (zone 6), where the temperature is 180°C. The barrel temperature zones are set as follows: Zone 1 165°C, Zone 2 180°C, Zone 3 195°C, Zone 4 205°C, Zone 5 205°C, Zone 6 195°C, and the die head temperature is 205°C. The screw speed is 350 rpm. During melt extrusion, a two-stage vacuum devolatilization process is initiated, with a vacuum degree of 0.085 MPa. The extrudate is then underwater pelletized and dried at 80°C for 4 hours to obtain the moisture-resistant aging-resistant ABS material.
[0030] Example 5 The formulation consists of the following parts by weight: 72 parts bulk ABS resin, 12 parts high-resin ABS powder, 0.25 parts perfluorohexyl ethyl sulfonamide propyl betaine, 1.2 parts epoxy silane-modified hydrophobic fumed silica obtained in Preparation Example 2, 1.0 part calcium stearate, 0.7 parts composite antioxidant (proportioning as in Example 1), and 0.4 parts ethylene bis-stearamide.
[0031] The preparation method is the same as in Example 1.
[0032] Example 6 The formulation consists of the following parts by weight: 72 parts of bulk ABS resin, 12 parts of high-resin ABS powder, 0.25 parts of perfluorohexyl ethyl sulfonamide propyl betaine, 1.2 parts of epoxy silane-modified hydrophobic fumed silica obtained in Preparation Example 3, 1.0 part of calcium stearate, 0.7 parts of composite antioxidant (with the same proportions as in Example 1), and 0.4 parts of ethylene bis-stearamide.
[0033] The preparation method is the same as in Example 1.
[0034] Comparative Example 1 The formulation, by weight, consists of the following: 72 parts bulk ABS resin, 12 parts high-resin ABS powder, 1.2 parts epoxy-silane modified hydrophobic fumed silica, 1.0 part calcium stearate, 0.7 parts composite antioxidant (same proportions as in Example 1), and 0.65 parts ethylene bis-stearamide. This comparative example does not contain perfluorohexyl ethyl sulfonamide propyl betaine.
[0035] Preparation method: Add all components through the main feed port, and the remaining process parameters are the same as in Example 1.
[0036] Comparative Example 2 The formulation consists of the following parts by weight: 72 parts bulk ABS resin, 12 parts high-resin ABS powder, 0.25 parts perfluorohexyl ethyl sulfonamide propyl betaine, 1.2 parts unmodified hydrophobic fumed silica (AEROSIL R972 raw powder), 1.0 part calcium stearate, 0.7 parts composite antioxidant (same ratio as in Example 1), and 0.4 parts ethylene bis-stearamide.
[0037] The preparation method is the same as in Example 1.
[0038] Comparative Example 3 The formulation, by weight, consists of the following: 72 parts bulk ABS resin, 12 parts high-resin ABS powder, 0.25 parts perfluorohexyl ethyl sulfonamide propyl betaine, 1.2 parts epoxy silane-modified hydrophobic fumed silica, 0.7 parts composite antioxidant (same proportions as in Example 1), and 1.4 parts ethylene bis-stearamide. This comparative example does not add calcium stearate; instead, an equal amount of ethylene bis-stearamide is used to supplement the lubrication function.
[0039] Preparation method: Add all components through the main feed port, and the remaining process parameters are the same as in Example 1.
[0040] Comparative Example 4 The formulation consists of the following parts by weight: 72 parts bulk ABS resin, 12 parts high-resin ABS powder, 0.25 parts perfluorohexyl ethyl sulfonamide propyl betaine, 1.2 parts epoxy silane modified hydrophobic fumed silica, 1.0 part calcium stearate, 0.7 parts composite antioxidant (same ratio as in Example 1), 0.5 parts dicarbodiimide anti-hydrolysis agent (Stabaxol P), and 0.4 parts ethylene bis-stearamide.
[0041] Preparation method: Dicarbodiimide is premixed with other main feed components (bulk ABS resin, ABS high-resin powder, calcium stearate, composite antioxidant, ethylene bis-stearamide) and added through the main feed port. Perfluorohexyl ethyl sulfonamide propyl betaine and epoxy silane modified hydrophobic fumed silica are added through the side feed port. The remaining process parameters are the same as in Example 1.
[0042] Comparative Example 5 The formulation, by weight, consists of: 72 parts bulk ABS resin, 12 parts high-resin ABS powder, 0.7 parts composite antioxidant (same proportions as in Example 1), and 0.4 parts EBS. This comparative example does not contain perfluorohexyl ethyl sulfonamide propyl betaine, epoxy silane-modified hydrophobic fumed silica, or calcium stearate.
[0043] Preparation method: Add all components through the main feed port, and the remaining process parameters are the same as in Example 1.
[0044] Comparative Example 6 Prepared according to Example 1 of the published patent CN122278111A.
[0045] Performance testing: Notched impact strength: According to ISO 179-1 / 1eA standard, the specimen size is 80mm×10mm×4mm, with a V-notch and a pendulum energy of 4J.
[0046] Alternating damp heat test: according to GB / T 2423.4 standard, the conditions are 55℃ / 95%RH, each cycle is 12h (heating and humidification - high temperature and high humidity constant - cooling), for a total of 12 cycles. The impact strength retention rate is the percentage of the notched impact strength after aging to the notched impact strength before aging.
[0047] Color difference ΔE: Calculated according to the CIE2000 color difference formula, using a spectrophotometer, D65 light source, 10° observation angle, and taking the average of 5 measurements.
[0048] Water contact angle: According to GB / T 30693 standard, the sample is cut into a 10mm×10mm flat piece, and an optical contact angle measuring instrument is used. Deionized water is used, and the drop volume is 5μL. The average value of 5 points is taken.
[0049] Insulation resistance: According to UL859 standard, the sample is tested at 500V DC voltage after being subjected to damp heat treatment for 48 hours.
[0050] Tensile strength and retention rate: According to ISO 527-2 standard, the tensile strength before and after aging was tested and the retention rate was calculated after aging at 85℃ / 85%RH for 500h.
[0051]
[0052] FTIR and DSC comparative tests were performed on Example 1 and Comparative Example 2. FTIR used difference spectral analysis to subtract the ABS matrix signal; pure GPS-modified silica was measured at 912 cm⁻¹. -1 The characteristic peak of the epoxy group at that location showed an intensity decrease of more than 80% and a shift to a lower wavenumber of approximately 10 cm in Example 1. -1 Meanwhile, in Example 1, the SAN phase -C≡N stretching vibration peak (2237 cm⁻¹) was observed.-1 The displacement to lower wavenumbers is approximately 4 cm. -1 No changes were observed in Comparative Example 2. DSC measured the Tg of the SAN phase in Example 1 to be 112.3 °C, approximately 3.8 °C higher than that of Comparative Example 2 (108.5 °C). The results indicate a strong dipole-dipole interaction between the epoxy groups and the nitrile groups, effectively restricting the movement of SAN molecular chain segments. FTIR was performed on the aged samples from Example 1 and Comparative Example 3. Example 1 showed a Tg of 112.3 °C at 1560–1580 cm⁻¹. -1 The presence of -COO in calcium carboxylate is attributed to this. - The characteristic absorption peak of asymmetric stretching vibration is observed, and it is also present at 1400-1450 cm⁻¹. -1 Observed -COO - The symmetric stretching vibration peak was observed; no characteristic peak was detected in the corresponding region in Comparative Example 3; further ICP-OES analysis showed that after extraction with deionized water at 80°C for 2 hours, the extractable calcium content in Example 1 decreased by 38% compared to the initial value, confirming that Ca... 2+ By forming calcium carboxylate salts, it effectively participates in the neutralization reaction of degraded carboxylic acids during the wet heat aging process. As shown in the table of test results, the embodiments of this invention, through the construction of a three-tiered synergistic protection system of "surface dynamic hydrophobicity—phase boundary anchoring barrier—matrix oxidation autocatalytic blocking," achieve excellent performance in all aspects. In contrast, after removing the fluorocarbon surfactant in Comparative Example 1, the water contact angle plummeted to 87° / 74°, the impact retention rate was only 57%, and the insulation resistance dropped to 1.5 MΩ, indicating that without the surface hydrophobic barrier, a large amount of water vapor invaded the matrix, and the first line of defense collapsed. In Comparative Example 2, ordinary hydrophobic silica without epoxy modification replaced the modified product of this invention, and the impact retention rate dropped to 70%, with a significant decrease in the water contact angle after aging, proving that the lack of anchoring effect between epoxy groups and SAN nitrile groups prevents nanoparticles from effectively anchoring phase boundaries and blocking capillary permeation channels. After removing calcium stearate in Comparative Example 3, the color difference increased significantly to 3.3, the insulation resistance dropped to 1.6 MΩ, and the impact retention rate was only 62%, confirming that Ca... 2+ The function of capturing oxidized carboxylic acids and blocking acidic autocatalytic cycles is irreplaceable. Comparative Example 4, after adding a carbodiimide anti-hydrolysis agent to Example 1, showed a comprehensive deterioration in performance, with an impact retention rate of only 53%, a color difference as high as 5.0, and an insulation resistance dropping to 0.8 MΩ. This strongly demonstrates that the carbodiimide solution targeting the hydrolysis of PC / ABS ester bonds is ineffective against pure ABS. Comparative Example 5, using only conventional antioxidants and lubricants, exhibited the worst performance across all indicators, with an impact retention rate of only 45% and an insulation resistance of only 0.6 MΩ. This fully illustrates that a simple antioxidant compound is completely inadequate to cope with the harsh alternating humid and hot conditions of a bathroom hair dryer. Comparative Example 6, with its commercially available water-resistant ABS product, showed an impact retention rate of 59% and an insulation resistance of only 1.0 MΩ, barely reaching the lower limit of the standard, indicating that its overall performance was significantly inferior to that of this invention.
[0053] The above description is merely a preferred embodiment of the present invention and is not intended to limit the present invention in any way. Although the present invention has been disclosed above with reference to preferred embodiments, it is not intended to limit the present invention. Any person skilled in the art can make some modifications or alterations to the above-disclosed technical content to create equivalent embodiments without departing from the scope of the present invention. Any simple modifications, equivalent changes and alterations made to the above embodiments based on the technical essence of the present invention without departing from the scope of the present invention shall still fall within the scope of the present invention.
Claims
1. An ABS material resistant to damp heat aging, characterized in that, It is prepared from raw materials comprising the following components, in parts by weight: The bulk ABS resin contains 65-78 parts, with a rubber content of 15-18% and an acrylonitrile content of 28-32%. 8-18 parts of high-polymer ABS powder, with a polybutadiene content of 55-65%; 0.15-0.4 parts of fluorocarbon surfactant; 0.8-2.0 parts of epoxy-based silane-modified hydrophobic fumed silica; 0.8-1.5 parts of calcium stearate; 0.5-1.0 parts of compound antioxidant; Lubricant 0.3-0.6 parts; The epoxy-modified hydrophobic fumed silica is prepared by grafting fumed silica that has been surface-treated with dimethyl dichlorosilane with γ-glycidoxypropyltrimethoxysilane, and has an epoxy value of 0.15-0.25 mmol / g.
2. The ABS material resistant to damp heat aging according to claim 1, characterized in that, The fluorocarbon surfactant is a perfluoroalkyl betaine-type fluorocarbon surfactant.
3. The ABS material resistant to damp heat aging according to claim 2, characterized in that, The perfluoroalkyl betaine fluorocarbon surfactant is perfluorohexylethylsulfonamide propyl betaine.
4. The ABS material resistant to damp heat aging according to claim 1, characterized in that, The composite antioxidant is composed of hindered phenolic antioxidant 1076, phosphite antioxidant 168 and ultraviolet absorber UV-234 in a mass ratio of (0.2-0.4):(0.2-0.4):(0.1-0.2).
5. The ABS material resistant to damp heat aging according to claim 1, characterized in that, The lubricant is ethylene bis-stearamide.
6. The ABS material resistant to damp heat aging according to claim 1, characterized in that, The preparation method of the epoxy silane modified hydrophobic fumed silica is as follows: 100 parts of fumed silica raw powder surface-treated with dimethyl dichlorosilane and 1.5-3 parts of γ-glycidyl etheroxypropyltrimethoxysilane are refluxed in toluene for 3-5 hours, filtered, and dried at 60-100℃ to obtain the product.
7. A method for preparing an ABS material resistant to damp heat aging as described in any one of claims 1 to 6, characterized in that, The melt blending extrusion using a twin-screw extruder includes the following steps: (1) Add bulk ABS resin, ABS high-rubber powder, calcium stearate, composite antioxidant and lubricant to the twin-screw extruder through the main feed port; (2) Fluorocarbon surfactant and epoxy silane modified hydrophobic fumed silica are added at the end of the plasticizing section through the side feed port. The temperature of this section is 180-200℃. (3) During the melt blending extrusion process, the barrel vacuum degree is ≥0.085MPa and the die head temperature is 200-215℃; (4) The extrudate is granulated underwater and dried to obtain the ABS material that is resistant to damp heat aging.
8. The preparation method according to claim 7, characterized in that, The twin-screw extruder has a screw speed of 350-450 rpm and a barrel temperature zone of 160-180℃ for the feeding section, 190-210℃ for the plasticizing section, and 185-195℃ for the homogenizing section.
9. The application of the moisture- and heat-resistant ABS material of claim 1 in a non-electrified structural component of a hair dryer that operates intermittently in a bathroom environment, wherein the non-electrified structural component is a nozzle, handle housing, or decorative ring.
Citation Information
Patent Citations
PC / ABS alloy with high weather resistance, hydrolysis resistance and antistatic property, and preparation method thereof
CN111004489A
Boiling-resistant ABS composite material as well as preparation method and application thereof
CN122278111A
